-18=3(-a+6)+2z

Simple and best practice solution for -18=3(-a+6)+2z equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -18=3(-a+6)+2z equation:


Simplifying
-18 = 3(-1a + 6) + 2z

Reorder the terms:
-18 = 3(6 + -1a) + 2z
-18 = (6 * 3 + -1a * 3) + 2z
-18 = (18 + -3a) + 2z

Solving
-18 = 18 + -3a + 2z

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '3a' to each side of the equation.
-18 + 3a = 18 + -3a + 3a + 2z

Combine like terms: -3a + 3a = 0
-18 + 3a = 18 + 0 + 2z
-18 + 3a = 18 + 2z

Add '18' to each side of the equation.
-18 + 18 + 3a = 18 + 18 + 2z

Combine like terms: -18 + 18 = 0
0 + 3a = 18 + 18 + 2z
3a = 18 + 18 + 2z

Combine like terms: 18 + 18 = 36
3a = 36 + 2z

Divide each side by '3'.
a = 12 + 0.6666666667z

Simplifying
a = 12 + 0.6666666667z

See similar equations:

| (7x^2-8)+(3x^2+1)= | | 13-4z=2z+9 | | 2x+2=-3x+6 | | 2x+2=4x+-6 | | cos(7x+ln(5x))=0 | | lx^2+3x+1l=1 | | 9-3x+2=10-3x | | 20+0.07(x-20)=0.06x | | 3u^2+3v^2-6uv+20u-20v+12=0 | | 1x-3y=14 | | Xy-4x+10=0 | | 9x+11=5x+1 | | 20+0.07x=0.06x | | x+9+2x=30 | | 11+2a=14 | | 3p=60+8p | | .2(x+100)=10 | | (-12)+6/2= | | 59-6x=3x+16 | | 20x+50b=320 | | -3x-y=17 | | 120+12x=545 | | 9x-2-4x-13=30 | | 4x^2-100x+625=0 | | x^2+20x+225=0 | | 4x-1=15x+1 | | 7x-6=58 | | 6x+29=Y | | x-16=-35 | | X+(3+X)=43 | | 150=3x^2 | | 2x+2=-4x+56 |

Equations solver categories